Application status quo and thinking of narrative medicine in geriatrics teaching - Huichan Yuan; Yahui Wang; Ruizhen Zhao; Bin Luo; Jing Chen; Kai Lv (Guoji laonian yixue zazhi)
Narrative medicine emphasizes the social, relational, and psychological dimensions of patient care, fostering students’ development in areas such as empathy, humanistic values, self-reflection, psychological resilience, moral beliefs, professional integrity, and the ability to build harmonious interpersonal relationships. Through literature review, it reveals that the integration of narrative medicine in geriatrics education remains limited. This article reflects on the unique characteristics of geriatrics education and examines the potential role of narrative medicine in enhancing its teaching methods. Through this exploration, we aim to provide insights and guidance for developing more effective educational approaches in geriatrics using narrative medicine.